THE MODEL OF INTELLECTUAL CAPITAL AND EMPLOYEES PERFORMANCE - Rakhmat Kabul, Eka; Ganda Wijaya, Harry; Limakrisna, Nandan (Dinasti International Journal of Management Science, 2021)
This research focused on higher of job rejection result and low of coordination among unit in problem solving of all the projects which is tend to decline of employees performance. The main issues discussed in this reseach is factors influence it, namely human procurement ,development and intellectual capital.The research aims to analyze, describe and test the impact of human procurement, development on intellectual capital and its implication on employees performance at PT. Dirgantara Indonesia. The research used was descriptive and explanatory survey method, so the research attempts to collect, present, analyze, and test hypotheses, to make a consclusions were used Structural Equation Model (SEM) approach. The design of study is a survey reseach, the unit analysis selected were core knowledge worker with a sample size of 303 from 1245 employees, based on Slovin’s formula. The results indicated that human procurement, development have a simultaneously positive and significant effect on intellectual capital, and human procurement, development are either partialy or simultaneously have a positive and significant effect on employees performance level throught intellectual capital. The findings are:(1) human procurement indicates low contribution on either intellectual capital or employees performance, the highest score of human procurement dimension is selection and the lowest is recruitment dimension. 2) human development indicates low contribution on either intellectual capital or employees performance, the highest score of human development dimension is education and the lowest is training dimension (3) intellectual capital indicates moderate scores on employees performance level, the highest score of intellectual capital dimension is social capital and the lowest is structure capital dimension. (4) the highest score size of employees performance dimension based on employees perception is goal and the lowest is motive dimension.